Recent Advances in the Field of Ventricular Assist Devices - Komamura, Kazuo (IntechOpen, 2013)
Recent Advances in the Field of Ventricular Assist Devices covers recent various advances and developments relating to ventricular assist devices and their diverse complications. Firstly, we overview recent technical advances as well as current indications, clinical outcomes, and countermeasures against complications, and furthermore, the latest techniques to identify clinical effectiveness at the patient's bedside. Secondly, we elucidate the current status of countermeasures against gastrointestinal bleeding, and current research on allosensitization during the usage of continuous flow pump. Finally, we explore the possibility of a new adjunct therapy in combination with ventricular assist devices. We hope that this book will provide valuable and up-to-date information on research and clinical use of ventricular assist devices.